Promising Methods and Systems of Quality Control of Innovative Bast Raw Material - Holovenko, T.M.; Yanyuk, T.I.; Boyko, G.A.; Dyagilev, A.S.; Shovkomud, O.V. (Science and Innovation, 2024)
Introduction. In advanced economies, oilseed flax is used not only for obtaining seeds, but also as a source of additional high-quality textile raw materials. In Ukraine, oilseed flax is the only domestic raw material resource that can become an alternative to imported cotton and fiber flax used for the textile and pulp-and-paper industries and for the production of reinforced composite materials. The analysis of the status of standardization of products from oilseed flax stems indicates the absence of regulatory documents to determine their quality. Therefore, the development of such regulations and standards is a pressing problem of our time, inasmuch as the organization of processing and the implementation of these products in the conditions of the present-day market and customer requirements are impossible without appropriate standardization and certification. Problem Statement. The need to develop standards for products from oilseed flax stems to determine their quality and commercial characteristics is urgent, since the approval of such technical specifications at the government level stimulates the creation of markets for the sale of oilseed flax straw as raw materials for the production of fibers that have a wide industrial application. Purpose. To develop domestic regulatory documents in order to control the quality of "new generation" bast raw material — oilseed flax straw — taking into account the modern consumer requirements. Materials and Methods. Based on the qualimetry methods, a complex methodology for determining the general quality of oilseed flax straw as an industrial raw material has been developed. Results. Technical specifications TU U 01.1-2303511525 - 001: 2016 Oilseed Flax Straw. Technical Specifications have been developed and approved at the state-owned enterprise Khersonstandartmetrologia. Conclusions. The certified domestic raw materials made of oilseed flax straw can be used in textile, pulp-and-paper and other industries of Ukraine for the manufacture of innovative competitive products of various functional purposes.